2020
DOI: 10.1111/jog.14302
|View full text |Cite
|
Sign up to set email alerts
|

Fertility‐sparing treatment for early‐stage epithelial ovarian cancer: Contemporary oncologic, reproductive and endocrinologic perspectives

Abstract: Aim Epithelial ovarian cancer (EOC) can be a devastating diagnosis in women of reproductive age who desire future fertility. However, in early‐stage disease, fertility‐sparing surgery (FSS) can be considered in appropriately selected patients. Methods This is a narrative descriptive review of the recent literature on FSS for EOC from oncologic, reproductive and endocrinologic perspectives. Results The recurrence rate following FSS performed for stage I EOC in published retrospective studies collectively is 13%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 114 publications
3
9
0
3
Order By: Relevance
“…Previous studies have considered cases with high-grade tumors, and stage IC tumors to have a higher risk of relapse and mortality, and that they could not be considered for a fertility-saving approach. However, recent studies showed that there is no clear evidence to support the fact that radical surgery in stage I EOC of any grade could improve patients' oncological outcomes (9)(10)(11)(12)(13)(14) , which supports our findings on the benefits of FSS after application of strict precautions and inclusion criteria of patients. Fruscio et al confirmed our findings (10) .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Previous studies have considered cases with high-grade tumors, and stage IC tumors to have a higher risk of relapse and mortality, and that they could not be considered for a fertility-saving approach. However, recent studies showed that there is no clear evidence to support the fact that radical surgery in stage I EOC of any grade could improve patients' oncological outcomes (9)(10)(11)(12)(13)(14) , which supports our findings on the benefits of FSS after application of strict precautions and inclusion criteria of patients. Fruscio et al confirmed our findings (10) .…”
Section: Discussionsupporting
confidence: 85%
“…Fruscio et al confirmed our findings (10) . Mandelbaum et al showed that oncologic outcomes after FSS were nearly similar to radical surgery in females with stage I, grade 1 and 2 EOC with serous, mucinous or endometrioid histology (9) . Jiang et al showed that cancer specific survival rate was better in the FFS group than that in the radical surgery group; which results from the fact that most high risk patients with higher grade tumors and clear cell morphology underwent radical surgery in their studies (11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was an overall successful pregnancy rate of 59%, which is comparable to a number of other studies which quote ranges of 54–67% [ 6 , 19 ]. The IVF rate of (12%) was comparable to other studies, but markedly higher than the general population [ 20 , 21 ]. The need for IVF is believed to be due to reduced ovarian reserve and alterations to pelvic anatomy following surgery [ 21 ].…”
Section: Discussionsupporting
confidence: 81%
“…In ovarian cancer, the prognosis for recurrence in the preserved ovaries after fertility-conserving treatment is good if radical surgery is performed again [ 61 ], and all six cases of EAOC (OEC and OCCC) have been reported to be cured [ 62 ]. That is, these recurrences may not be the result of hematogenous metastasis or intra-abdominal dissemination, but rather, the tumor cells may remain in the genital tract and be transported from the endometrium to the ovaries.…”
Section: Reconsideration Of the Developmental Mechanism Of Eaoc Bamentioning
confidence: 99%